Oil Film Thickness and Meshing Efficiency for a Novel Closed Movable Tooth Gear Reducer - Shuo Yang; Lizhong Xu (Lubricants)
Equations are developed for the relative sliding velocities, entrainment velocities, forces, friction coefficients, effective radius of curvature, oil film thickness, friction loss, and meshing efficiency for a novel closed movable tooth gear reducer. Using these equations, the relative sliding velocities and entrainment velocities of the reducer are studied. The meshing efficiencies and their changes along with meshing positions and main parameters are analyzed. Changes of the meshing efficiencies along with load torque are also studied. An efficiency experiment of the reducer prototype is carried out. Results indicate that the meshing efficiency of the novel closed reducer increases with increasing eccentric distance. When an error in the eccentric distance occurs, the meshing efficiency is significantly reduced. The measured efficiency is close to the calculated one, supporting the theoretical studies.